ANALYSIS OF TAXPAYER FACTORS ON THE USE OF BATAM CITY E-FILING - Juanda Stephane Situmeang; Neni Marlina Br. Purba (SEAN Institute, 2022)
The Directorate General of Taxes has carried out extensification efforts, one of which is by increasing the number of taxpayers while intensifying efforts by increasing tax revenues. Research is quantitative. Sampling using Slovin got 100 respondents. The Likert scale used. The results of this study use SPSS form 25. The convenience variable which is emphasized by the t-count value of 6.224 has exceeded 1.984 which is the t-table value at probability 0.05 and the significance value for the convenience variable is 0.000 does not exceed 0.05, the convenience variable has an effect significant to e-filing users. The security variable which is confirmed by the calculated t value of 2.442 has exceeded 1.984 which is the t table value at probability 0.05 and the significance value for the knowledge variable is 0.005 and does not reach 0.05. the security variable has a significant impact on the utilization of e-documenting. The information technology readiness variable which is confirmed by the t value of 6.597 has exceeded 1.988 which is the t table value at probability 0.05 and the significance value for the information technology readiness variable is 0.000 and does not reach 0.05, the information technology readiness variable has a significant influence on use of e-filing. Simultaneously give effect to the dependent variable. In other words, the variables of convenience, security and readiness of information technology have a huge impact all the while on the variable of needing to utilize e-documenting.